Violation of Cooperative Principle in Court Context - Maharani Riestania (Passage, 2017)
The present study explores exchanges in a court trial based on the theory of cooperative principle (CP). This study aims to examine how a defendant violates the cooperative principle during an investigation in a trial. In addition, this study also seeks to analyze the perlocutionary effect of the violation on the prosecutors. The data comprise transcripts of conversations between a defendant and seven prosecutors with regard to the cyanide court case in the 21st court session. The data were analyzed qualitatively by using Grice’s (1975) theory of cooperative principle. Austin’s (1962) account of the perlocutionary act is also used to examine the effect of the violation. The findings show that the defendant violated the cooperative principle through violation of (1) the quality maxim alone and (2) the quality maxim aided with a breach of other maxims (quantity, relation or manner).Violations of the quality maxim alone were committed by giving negative answers and showing lack of memory. Meanwhile, violations of the quality maxim aided with the breach of other maxims were committed by giving irrelevant aspects of information and conveying convoluted answers. With regard to perlocutionary effect on the prosecutors, the violations gave rise to certain responses from the prosecutors, i.e. repeating the questions, revealing the facts, complaining about the defendant’s answers, and directing the defendant to admit the truth. The perlocutionary effect indicates that although violations of the cooperative principle might help the defendant to hide the truth in her answers, the prosecutors did not accept the answers easily. The prosecutors appeared to base their responses more on the information that they had gained previously.Keywords: cyanide court case, cooperative principle, violation, perlocutionary act